The ceiling in the Mandapa of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
The ceiling in the mandapa (pillared hall) of the Shiva Temple is made up of plain concentric circular rings that are offset from each other. At the centre of the dome is a small lotus medallion. There are eight pillars that support this domical ceiling. The brackets of these pillars have bharavahaka (load bearers) sculptures.